Pengaruh Kepemilikan Asing dan Profitabilitas terhadap Pengungkapan Corporate Social Responsibilty (CSR) pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI - S Sunreni (SAFE-Network, 2022)
This study aims to determine the effect of foreign ownership and profitability on disclosure of corporate social responsibility in mining sector companies listed on the Indonesia Stock Exchange (IDX). The sample selection method uses purposive sampling to obtain a sample of 9 companies from 40 mining sector companies listed on the IDX. The type of data used is secondary data in the form of annual financial report data, which is in 2012 2016. The analysis used is hypothesis testing with alpha (0.05). Based on the results of partial hypothesis testing obtained that foreign ownership has a significant effect on disclosure of Corporate Social Responsibility (CSR), profitability has no significant effect on CSR disclosure. While simultaneously obtained that foreign ownership and profitability together have a significant effect on CSR disclosure.